Understanding domestic savings: an empirical approach. Issue 9 (19th February 2020) - Cerda, Rodrigo; Fuentes, Rodrigo; García, Gonzalo; Llodrá, José I.
ABSTRACT: There are two unusual and important features in the evolution of the savings rate in Chile. First, the economy increased the average savings rate by 11 percentage points in the period 1985–2013 compared to 1960–1984, mainly due to a large change in private savings rate (10 percentage points), and an additional 1 percentage point from the public sector. The second feature is related to the change in the composition of private savings. After several years of nearly no corporate savings, this component became an important part of total savings reaching an average of almost 10% of Gross National Disposable Income (GNDI) during the period 1986–2012. Our results show that the 1984 tax reform, the boost in the marginal productivity of capital and the deepening of the financial market were the main drivers that explain the dramatic increase in corporate savings. We also found that the reduction in personal income tax after the tax reform and the higher income per capita growth helped to explain the increase in household savings, while the structural balance rule helped to explain the increase in public savings.